Anatomical subgroup analysis of the MERIDIAN cohort: ventriculomegaly. (5th November 2017) - Griffiths, P. D.; Brackley, K.; Bradburn, M.; Connolly, D. J. A.; Gawne‐Cain, M. L.; Griffiths, D. I.; Kilby, M. D.; Mandefield, L.; Mooney, C.; Robson, S. C.; Vollmer, B.; Mason, G.
ABSTRACT: Objective: To assess the contribution of fetal magnetic resonance imaging (MRI) in fetuses of the MERIDIAN cohort diagnosed with ventriculomegaly (VM) as the only abnormal intracranial finding on antenatal ultrasound. Methods: This was a subgroup analysis of the MERIDIAN study of fetuses with only VM diagnosed on ultrasound in women who had a subsequent MRI examination within 2 weeks and for whom outcome reference data were available. The diagnostic accuracy of ultrasound and MRI was reported in relation to the severity of VM. The difference in measurements of trigone size on the two imaging methods and the clinical impact of adding MRI to the diagnostic pathway were also studied. Results: In 306 fetuses with VM, ultrasound failed to detect 31 additional brain abnormalities, having an overall diagnostic accuracy of 89.9% for ultrasound, whilst MRI correctly detected 27 of the additional brain abnormalities, having a diagnostic accuracy of 98.7% ( P  < 0.0001). There were other brain abnormalities in 14/244 fetuses with mild VM on ultrasound (diagnostic accuracy, 94.3%) and MRI correctly diagnosed 12 of these (diagnostic accuracy, 99.2%; P  = 0.0005). There was a close agreement between the size of trigones measured on ultrasound and on MRI, with categorical differences in only 16% of cases, showing that MRI did not systematically overestimate or underestimate trigone size. Complete prognostic data were available in 295/306 fetuses and the prognosis category changed after MRI in 69/295 (23.4%) cases. The overall effect of MRI on clinical management was considered to be 'significant', 'major' or 'decisive' in 76/295 (25.8%) cases. Conclusion: Our data suggest that a woman carrying a fetus with VM as the only intracranial finding on ultrasound should be offered an adjuvant investigation by MRI for further evaluation. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.